Mengungkap kelestarian pertanian kecil Melayu pada zaman penjajahan British - Mohd Azlan Abdullah,; Rosmiza Mohd Zainol,; Rosniza Aznie Che Rose,; Amriah Buang, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2009)
This paper applies Buttimer’s 2001 conception of sustainable lifeway (genre de vie), which integrates and harmonises the objectives of ecological integrity, economic growth and social vitality to the experience of Malay farmers in British Malaya (1874-1948). It was found that British colonial capitalism had structurally transmuted the indigenous farmers’ lifeways: they now became small-scale subsistence farmers vis-à-vis the colonial large-scale commercial planters. This newly acquired inferior status justified the discrimination and marginalisation of the Malay farmers by the colonial administration as witnessed their agricultural land, financial and R&D development policies. Yet, against all these odds the small-scale Malay farmers had proven their resillience. As rice cultivators and coconut smallholders they managed to feed the entire non-farming population of the colony. As rubber smallholders they managed to compete with the privileged colonial planters. At the latter part of the colonial administration , however, the long suffering Malay small farmers benefited from the benefiction of a more socialist oriented cadre of colonial administrators. The latter went through lengths and breadths to strengthen the Malay Reserve Land Enactment which thus ensured a geopolitical basis for the sustainability of the Malay small-scale farmers.